2007
DOI: 10.1021/jp066730w
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Effects on Structure and Photophysical and Photoelectrochemical Properties of Fullerene Dendrimers and Their Nanoclusters

Abstract: Multifullerene-terminated dendrimers Gn (n ) 1-5) were synthesized and structural, photophysical, and photoelectrochemical properties were studied for the fullerene dendrimers and their nanoclusters. The fullerene dendrimers formed clusters when toluene solutions of the fullerene dendrimers were injected into acetonitrile. Dynamic light scattering and atomic force and scanning electron microscopic measurements on these clusters revealed that the cluster size decreased with increasing the generation number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 103 publications
3
44
0
Order By: Relevance
“…However, controlling the morphology and size of the superstructures is not well understood. A recent report showed that the morphology of self‐organized clusters of various dendritic fullerenes has an influence on their macroscopic properties, such as the size‐dependent photovoltaic response 7. Recently, we explored the polymorphism of fullerene assemblies by using the two different intermolecular forces, namely π–π interactions of C 60 and van der Waals interactions of aliphatic chains 8.…”
mentioning
confidence: 99%
“…However, controlling the morphology and size of the superstructures is not well understood. A recent report showed that the morphology of self‐organized clusters of various dendritic fullerenes has an influence on their macroscopic properties, such as the size‐dependent photovoltaic response 7. Recently, we explored the polymorphism of fullerene assemblies by using the two different intermolecular forces, namely π–π interactions of C 60 and van der Waals interactions of aliphatic chains 8.…”
mentioning
confidence: 99%
“…The whole series of t-butyl-protected dendrons have been subject of photoelectrochemical measurements. Preliminary experiments by injection of toluene solutions containing the appropriate dendron into acetonitrile resulted in the formation of large clusters in the solvent mixture [30]. The order of the mean diameters was not consistent with that of their molecular sizes ranging from 790 nm for (29) m to 90 nm for (36) m .…”
Section: Pamam G4mentioning
confidence: 92%
“…66 The IPCE value of the SnO 2 /(4) m devices was increased with increasing the generation number. The maximum IPCE value of 6% in the SnO 2 /(4e) m device was achieved at 400 nm at an applied potential of 0.11 V vs SCE.…”
Section: Dendrimersmentioning
confidence: 95%
“…However, the IPCE value was not improved relative to that of the SnO 2 /(4) m device. 66 This may result from the rather large steric congestion around the C 60 moieties of 4, rendering it difficult to yield suitable complexation between the porphyrin and C 60 within 4.…”
Section: Dendrimersmentioning
confidence: 99%